Active DNA demethylation—The epigenetic gatekeeper of development, immunity, and cancer - Rahul Prasad; Timothy J. Yen; Alfonso Bellacosa (Advanced Genetics, 2021)
Abstract DNA methylation is a critical process in the regulation of gene expression with dramatic effects in development and continually expanding roles in oncogenesis. 5‐Methylcytosine was once considered to be an inherited and stably repressive epigenetic mark, which can be only removed by passive dilution during multiple rounds of DNA replication. However, in the past two decades, physiologically controlled DNA demethylation and deamination processes have been identified, thereby revealing the function of cytosine methylation as a highly regulated and complex state—not simply a static, inherited signature or binary on‐off switch. Alongside these fundamental discoveries, clinical studies over the past decade have revealed the dramatic consequences of aberrant DNA demethylation. In this review we discuss DNA demethylation and deamination in the context of 5‐methylcytosine as critical processes for physiological and physiopathological transitions within three states—development, immune maturation, and oncogenic transformation; and we describe the expanding role of DNA demethylating drugs as therapeutic agents in cancer.